PEMBATALAN PADA PERJANJIAN YANG TIDAK MENGGUNAKAN BAHASA INDONESIA (STUDI KASUS PUTUSAN NOMOR 450/PDT.G/2012 / PN.JKT.BAR) - Thomas Aryanto G; Stanislaus Atalim (Jurnal Hukum Adigama, 2018)
Starting from the treaty agreement from national agreement to international agreement, with the existence of the development of the time of course there are many developments including in the development in the field of agreement. in this journal the author explains about how should the implementation of Article 31 of Law Number 24 Year 2009 concerning about Flags, Languages, and Symbol of Country and National Anthem should be applied in Indonesia. the authors raise this issue using case studies on decision number 450 / Pdt.G / 2012 / PN Jkt.Bar where PT Bangun Karya Pratama Lestari sued Nine AM Ltd. to cancellation agreements that only use the English language without using the Indonesian language. in this case the panel of judges decides that the agreement is null and void because it violates Article 31 of Law Number 24 Year 2009 because the judges consider the agreement to violate Article 1320 Paragraph (4) of the Civil Code which reads "a lawful cause" this article of judges misinterpreted the exclusion of the law on the promulgation of the treaty. in the old legal books says that is not to violate the law is to the purpose of making a treaty not on the written evidence of a covenant that is only evidence when there is a dispute between the covenant makers. a covenant is not a written matter but the treaty itself is an agreement executed and agreed upon by both parties to fulfill the agreed agreement.